Business Development Plan for Surya Super Crab Restaurant in Makassar City - Syamsul Bahri Hunou (Scientia Integritas Utama, 2023)
The seafood restaurant had become an important segment in the culinary industry that was continuously growing. The consumption of seafood has been increasing globally as people have been increasingly appreciating the unique flavors, health benefits, and culinary experiences offered by seafood dishes. This research aimed to develop the appropriate business development strategy, including opening new branches with minimal capital. The research method used was a qualitative descriptive analysis method supported by quantitative analysis based on primary and secondary data. Primary data was obtained through interviews with business owners and customer surveys. Secondary data was obtained from literature reviews, including books, articles, journals, websites, and social media. The customer empathy mapping analysis results showed that Surya Super Crab Restaurant customers had been highly engaged with social media. The analysis of the business model canvas indicated that certain business model components had required additional development. The financial feasibility of the business, based on the Net Present Value (NPV) of Rp Rp. 126.186.850, Internal Rate of Return (IRR) of 25,45%, and Payback Period (PP) of 4 years and 1 month, demonstrated that all financial feasibility requirements had been met.